Bezpieczeństwo jako dobro wspólne - Czuryk, Małgorzata (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
One of the most important concepts of the axiological character used by the legislator is the concept of the common good. This axiology, however, does not deprive the common good of being a constitutional value for its normative content. Despite the fact it is not deprived of normative content, there are some difficulties in decoding it, which result from a large scope of generalization of the concept. Within the concept of the common good, we can distinguish security, which is of a social and public value, not just an individual one. Ensuring security presented as the mutual goal of the state and its authorities can therefore be seen through the lens of common good.